2017
DOI: 10.1002/path.4991
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus E6 protein enriches the CD55(+) population in cervical cancer cells, promoting radioresistance and cancer aggressiveness

Abstract: Accumulating evidence indicates that the human papillomavirus (HPV) E6 protein plays a crucial role in the development of cervical cancer. Subpopulations of cells that reside within tumours are responsible for tumour resistance to cancer therapy and recurrence. However, the identity of such cells residing in cervical cancer and their relationship with the HPV-E6 protein have not been identified. Here, we isolated sphere-forming cells, which showed self-renewal ability, from primary cervical tumours. Gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Our previous report suggested that a cluster of differentiation (CD) marker, CD55, was upregulated in primary cervical cancer sphere cells. An enriched CD55 þ subpopulation was found in human papillomavirus (HPV)positive and HPV-E6-overexpressing clones that contributed to the aggressiveness of the cervical cancer cells (14). In this study, we identified CD71 as another potential cell surface marker that is also associated with the expression of the HPV-E6 protein.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our previous report suggested that a cluster of differentiation (CD) marker, CD55, was upregulated in primary cervical cancer sphere cells. An enriched CD55 þ subpopulation was found in human papillomavirus (HPV)positive and HPV-E6-overexpressing clones that contributed to the aggressiveness of the cervical cancer cells (14). In this study, we identified CD71 as another potential cell surface marker that is also associated with the expression of the HPV-E6 protein.…”
Section: Introductionmentioning
confidence: 86%
“…For CRISPR/ Cas9 gene editing, SiHa cells were cotransfected with gRNA (GeneArt CRISPR U6 Strings DNA gRNA, Life Technologies) and Cas9 mRNA (GeneArt CRISPR Nuclease mRNA) using Lipofectamine 3000. The experimental procedures were performed as described previously (14). In addition, the potential off-targets were predicted using CRISPOR (http://crispor.org) and the Zhang Laboratory tool (MIT 2015; http://crispr.mit.edu/).…”
Section: Crispr Knockout Of the Cd71 Genementioning
confidence: 99%
“…We have demonstrated that CD55 is upregulated in spheroid cells derived from primary cervical cancer tissue and that these cells display a highly expressed 'dry' gene, suggesting that cervical cancer tissue may contain cells with CSC properties [37]. In recent years, mCRPs CD46, and CD55 have demonstrated that CD59 and CD59 are important factors in tumorigenesis in various types of tumors [38]. CRISPR / Cas9 targeting of CD55 may be able to completely abolish the oncogenic function of CD55 and enable radiation therapy of cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The viral and host (patient) gene expression profiles of the 20 HPV16‐positive RNA‐seq data further suggest that the E2 and E7 genes of HPV, but not E6, play a major role in HPV‐induced HNSCC. The molecular mechanism of HPV oncogenesis in HNSCC differs from what has been reported in cervical carcinogenesis (Leung et al ., ). The viral/host gene expression profiles of HPV‐induced HNSCC elucidate HPV oncogenesis in HNSCC.…”
Section: Introductionmentioning
confidence: 97%